2005
DOI: 10.1093/molehr/gah246
|View full text |Cite
|
Sign up to set email alerts
|

IDO expression on decidual and peripheral blood dendritic cells and monocytes/macrophages after treatment with CTLA-4 or interferon-γ increase in normal pregnancy but decrease in spontaneous abortion

Abstract: Recent data demonstrated that CD4+CD25+ regulatory T (Treg) cells and an enzyme called indoleamine 2,3-dioxygenase (IDO) mediate maternal tolerance to the fetus. Interestingly, Treg cells express the CTLA-4 molecule on their surface, and B7 (CD80/86) ligation by CTLA-4 enhanced IDO activity of dendritic cells (DCs) and monocytes by the induction of interferon gamma (IFN-gamma) production. In this study, we studied the IDO expression on peripheral blood monocytes and decidual monocytes or DCs after treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(151 citation statements)
references
References 27 publications
6
141
1
Order By: Relevance
“…The direct effect of abatacept binding to CD80/86 on APCs remains a topic of controversy (37,38,(48)(49)(50). While some studies have demonstrated that CTLA-4Ig induced the up-regulation of IDO in DCs, which subsequently modulated T cell activation, our data and other transcriptional data have failed to confirm this (37,38).…”
Section: Discussioncontrasting
confidence: 59%
“…The direct effect of abatacept binding to CD80/86 on APCs remains a topic of controversy (37,38,(48)(49)(50). While some studies have demonstrated that CTLA-4Ig induced the up-regulation of IDO in DCs, which subsequently modulated T cell activation, our data and other transcriptional data have failed to confirm this (37,38).…”
Section: Discussioncontrasting
confidence: 59%
“…Reflecting remarkable plasticity, CD14 1 myelomonocytic cells efficiently respond to various environmental stimuli, particularly the semi-allograft, which might induce the differentiation of these cells in a tissue-specific manner for immune regulation and host defense responses 2,[27][28][29] . Studies have shown that CD14 1 myelomonocytic cells, which intimately contact the embryo allograft, displayed a unique ability to promote immunotolerance via the induction of Tregs 2 .…”
Section: Discussionmentioning
confidence: 99%
“…23,44 In humans, however, CTLA-4 expressed in Treg cells up-regulates IDO expression on decidual and peripheral blood DC and monocytes by the induction of IFN-c production. 45 Decidual Treg seem to work by cell-cell contact 46 and suppression of Tcell responses. 47 Dr. Saito extensively revises the type of Treg present during pregnancy and discusses the importance of correctly identifying their phenotypes for future clinical applications.…”
Section: Tafurimentioning
confidence: 99%